Reseñas (1998)
José C. Moya, Cousins and Strangers; Spanish Immigrants in Buenos Aires 1850-1930. Berkeley-Los Angeles-London: University of California Press 1998. 567 páginas. /  Jeffrey Lesser: Welcoming the Undesirables: Brazil and the Jewish Question. Berkeley-Los Angeles-London: University of California Press 1995. 280 páginas.